2023
DOI: 10.3390/jcm12051712
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Geometrical Changes in Patients with Functional Tricuspid Regurgitation: Insights from a CT Scan Analysis Focusing on Commissures

Abstract: Background: Cardiac computed tomography (CT) provides important insights into the geometrical configuration of the tricuspid valve (TV). The purpose of the present study was to assess the geometrical changes of TV in patients with functional tricuspid regurgitation (TR) using novel CT scan parameters and to correlate these findings with echocardiography. Methods: This single-center study enrolled 86 patients undergoing cardiac CT and divided them into two groups according to the presence or not of severe TR (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, the incidence of RV failure after elective cardiac surgery is relatively low, occurring in approximately 0.1% of patients. On the other hand, in the context of heart transplant and left ventricular assist device (LVAD) implantation, the incidence significantly rises, reaching peak rates of 30-40% [2][3][4][5][6]. RV dysfunction has important clinical consequences; a study conducted by Bootsma et al involving 1109 cardiac patients demonstrated an independent association between RV dysfunction and 2-year all-cause mortality after heart surgery [7].…”
Section: The Clinical Problem: a Matter Of "Definition"mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the incidence of RV failure after elective cardiac surgery is relatively low, occurring in approximately 0.1% of patients. On the other hand, in the context of heart transplant and left ventricular assist device (LVAD) implantation, the incidence significantly rises, reaching peak rates of 30-40% [2][3][4][5][6]. RV dysfunction has important clinical consequences; a study conducted by Bootsma et al involving 1109 cardiac patients demonstrated an independent association between RV dysfunction and 2-year all-cause mortality after heart surgery [7].…”
Section: The Clinical Problem: a Matter Of "Definition"mentioning
confidence: 99%
“…The normal range for TAPSE is 20.7 mm ± 11.1 (SD) for males and 20.3 mm ± 8.6 (SD) for females, with values under 17 mm usually indicating some degree of dysfunction [52]. TAPSE has gained popularity thanks to its easy measurement and reproducibility [6,53,54]; however, it has some disadvantage, mainly because it does not detect regional dysfunction. Moreover, it is angle-dependent, load-dependent, and may be increased in the case of tricuspid regurgitation.…”
Section: The Role Of the Echocardiography: Tapse Rvef Rvfac Tdi Strai...mentioning
confidence: 99%